2014
DOI: 10.1021/ma501933s
|View full text |Cite
|
Sign up to set email alerts
|

Spiral and Mesoporous Block Polymer Nanofibers Generated in Confined Nanochannels

Abstract: Spiral-like or various porous polymer nanofibers have great applications in biosensor, bioengineering, and template-fabrication of functional inorganic materials. However, the fabrication of polymer nanostructures with controllable porous or spiral morphology in one process is a big challenge. Here we first demonstrated a general and easy method to generate spiral or porous block copolymer (BCP) nanofibers by using geometric confinement of nanochannels to disturb the self-assembly of BCP while nonsolvent is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Lee et al showed that pore modulations originated from self-induced current oscillations may be an starting point to create a well-defined 3D porous structure at a local scale [110]. Russell's [58,[131][132][133][134][135][136]; J. T. Chen's [45,137,138]; Z. Jin´s [139][140][141][142]; J. Lee´s [143]; J. Wang´s [144]; Marsal´s [145]; and more recently, by our group [71,100,[146][147][148][149][150][151][152][153][154][155][156] among other groups that will be mentioned along this section.…”
Section: Three-dimensional Porous Structures Three-dimensional (3d) mentioning
confidence: 96%
“…Lee et al showed that pore modulations originated from self-induced current oscillations may be an starting point to create a well-defined 3D porous structure at a local scale [110]. Russell's [58,[131][132][133][134][135][136]; J. T. Chen's [45,137,138]; Z. Jin´s [139][140][141][142]; J. Lee´s [143]; J. Wang´s [144]; Marsal´s [145]; and more recently, by our group [71,100,[146][147][148][149][150][151][152][153][154][155][156] among other groups that will be mentioned along this section.…”
Section: Three-dimensional Porous Structures Three-dimensional (3d) mentioning
confidence: 96%
“…Furthermore, similar polymer phase separations and transformation behaviors at the microscale have also been observed [34,35,36,37,38]. Because of the success of the AAO templating method, many publications have explored various AAO applications such as thermal and physical properties of polymer nanostructures under nanoconfinement conditions, fabrication of higher−order nanostructures, polymerization and crystallization in AAO templates, and the double infiltration nanoencapsulation process [39,40,41,42,43,44,45,46,47,48,49].…”
Section: Introductionmentioning
confidence: 97%
“…In a comparison, notwithstanding similar chiral structures could be observed from the selfassembly of achiral BCPs, it is usually challenging to achieve a preferred chirality. [40][41][42][43][44][45][46][47][48] Due to these interesting phenomena and the remaining challenges in BCP* self-assembly, it is of great emergency to retrospect the development of BCP* self-assembly and pinpoint the recent progress, which may be helpful for the future research in this field.…”
Section: Introductionmentioning
confidence: 99%